An early warning monitoring of Earthquake-induced slope failures by monitoring inclination changes in multi-point tilt sensors - L. Wang; S. Nishie; L. Su; H. Yamaguchi; S. Yamamoto; T. Uchimura; S.N. Tao (Lowland Technology International, 2018)
An early warning monitoring system is one of the most effective ways to reduce disasters induced by slope instability. The 2016 Ms 7.3 Kumamoto earthquake, which occurred in Kumamoto prefecture, Japan, induced more than 190 large scales of slope failures (123), debris flows (57) and landslides (10). A system of distributed tilt sensors for early warning monitoring of earthquake-induced landslides and slope failures has been proposed. Tilt angles in the surface layer of a slope were monitored using this method and, in several case studies, distinct behaviors in tilt angles in pre-failure stages were detected. Based on this behavior, it is recommended, from a regulatory perspective, a precaution be issued when the tilting rate of a slope is 0.01°/h, and a warning be issued when the tilting rate is 0.1°/h.